Search for large extra dimensions in final states containing one photon or jet and large missing transverse energy produced in pp̄ collisions at s=1.96TeV - Aaltonen, T; Adelman, J; Akimoto, T; Albrow, MG; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; et al. (2008)
We present the results of searches for large extra dimensions in samples of events with large missing transverse energy E T and either a photon or a jet produced in pp̄ collisions at s=1.96TeV collected with the Collider Detector at Fermilab II. For γ+E T and jet+E T candidate samples corresponding to 2.0 and 1.1fb-1 of integrated luminosity, respectively, we observe good agreement with standard model expectations and obtain a combined lower limit on the fundamental parameter of the large extra dimensions model MD as a function of the number of extra dimensions in the model. © 2008 The American Physical Society.